Open innovation in platform competition - LIN, Mei (Institutional Knowledge at Singapore Management University, 2010)
We examine the competition between a proprietary platform and an open platform,where each platform holds a two-sided market consisted of app developers and users.The open platform cultivates an innovative environment by inviting public efforts todevelop the platform itself and permitting distribution of apps outside of its own appmarket; the proprietary platform restricts apps sales solely within its app market. Weuse a game theoretic model to capture this competitive phenomenon and analyze theimpact of growth of the open source community on the platform competition. We foundthat growth of the open community mitigates the platform rivalry, and balances the developernetwork sizes on the two platforms. The platforms’ relative dominance is foundto be a key determining factor in the effect of open community growth in equilibrium.Furthermore, total surplus on the open platform and total welfare of the two platformsboth increase as the open community grows.